SELF-ASSESSMENT OF LEADERSHIP SKILLS OF NURSE MANAGERS AND RELATED FACTORS AT LEVEL 1 GENERAL HOSPITALS IN HO CHI MINH CITY IN 2023 - Ngo, Thanh Truc; Tran, Cong Toai (Cantho Journal of Medicine and Pharmacy, 2025)
Background: Nursing leadership plays an important role in facilitating and improving nursing performance, which is essential to providing quality care and ensuring patient safety, increasing satisfaction, reducing errors in care, and contributing to the happiness, commitment, and job satisfaction of the nursing workforce with the organization. Objectives: To assess the leadership skills of nurse managers and the factors related to leadership skills. Materials and methods: A cross-sectional descriptive study on 160 nurse managers at Level 1 General Hospitals in Ho Chi Minh City. Results: Leadership skills score of the nurse managers were average level (59.55 ± 10.45). The analysis results showed that there was no relationship between gender, management position, and leadership skills, respectively (p=0.552 and p=0.426). However, there was a significant relationship between the number of years working in a management position and leadership skills (p=0.001). Conclusion: There should be continuous training programs on leadership skills to provide nurse managers in order to promote their capacity and lead effectively.